PELAKSANAAN KAMPUS MENGAJAR SEBAGAI SARANA AKTUALISASI DIRI - Rusmi, Rusmi; Cahyani, Adelia Dwi; Katiyah, Katiyah; Yumna, Nada Laili Zayyani; Mahardhani, Ardhana Januar (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2022)
During the Covid-19 pandemic, learning cannot be applied optimally but using online. Over time, schools have implemented a new normal era by carrying out face-to-face learning by implementing health protocols. This is what makes the government hold Kampus Mengajar activities where students teach during the pandemic. The implementation of the Kampus Mengajar batch 3 provides opportunities for students to broaden their horizons and gain experience in helping the teaching and learning process in elementary schools. This paper will describe the activities in the Teaching Campus batch 3 carried out at SDN 5 Pohijo Ponorogo, namely in three activities including teaching and learning, technology adaptation, and school administration. The writing is described in descriptive form with data collection methods in the form of interviews, observations, and documentation. The results obtained in this Kampus Mengajar batch 3 are that students can actualize themselves to the maximum according to their respective fields of expertise, can transfer knowledge, and can help accelerate teachers and students in the process of adapting technology, so that positive collaboration can occur from this. between students, lecturers, and teachers in order to improve the quality of learning in SDN 5 Pohijo Ponorogo..